Jones v United Kingdom: The European Court of Human Rights Restricts Individual Accountability for Torture. Issue 79 (19th August 2014) - Ryngaert, C
In Jones and others v United Kingdom (2014), the European Court of Human Rights (ECtHR) ruled that granting immunity from jurisdiction to State officials in civil proceedings with respect to torture was not a violation of Article 6 ECHR. This is an unfortunate decision, as its application will often result in an accountability vacuum, as victims of torture may not have reasonable access to remedies in the State where they were tortured. Only bystander States, or their State of nationality could then offer relief by offering a forum. A proper avenue for such States is to make the exercise of jurisdiction and the conferral of immunity dependent on whether or not the territorial State offers an adequate forum for dispute-settlement. By further developing these principles, the notion that, under international law, persons are individually accountable for international crimes and should not be allowed to hide behind the State on whose behalf they act, could be finally realised.